Bahiagrass: A Quick Reference - Yoana C. Newman (EDIS)
SS-AGR-263, a 3-page fact sheet by Yoana C. Newman, provides prospective growers with basic information about this warm-season perennial forage, touching briefly on its origin, use, adaptation, management practices, fertilization, weed control, pests and control. Includes a table comparing varieties. Published by the UF Department of Agronomy, December 2007.